ANALISIS SUPPLY CHAIN PADA USAHA MIKRO: STUDI KASUS RICE BOWL TRUSTMEE DI KOTA METRO - Alhidayatullah, Alhidayatullah; Putri, Sastria; Hastarita, Nike; Rezki Regina, Amelia (Jurnal Inspirasi Ilmu Manajemen, 2025)
Research on supply chain analysis has been done a lot and tends to be only for large companies, while research on supply chains in micro businesses, especially in the culinary sector in Indonesia is still limited. This study aims to analyze the structure and flow of Rice Bowl Trustmee's supply chain, identify key challenges in supply chain management, evaluate strategies implemented to overcome these challenges, and provide recommendations to improve the efficiency and effectiveness of supply chain management in similar micro enterprises. This study uses a qualitative approach with a case study method. Data is collected through in-depth interviews with business owners, operational managers, suppliers, and customers, as well as direct observation of operational processes. Data analysis techniques include data reduction, data presentation, thematic analysis, and conclusion drawing to ensure the accuracy and consistency of research findings. The results of the study stated that Rice Bowl Trustmee implements a simple supply chain involving local raw material suppliers, order-based production, temporary storage, distribution through online services, and digital promotion. The main challenges faced include limited storage capacity, dependence on a single supplier, and fluctuations in market demand. Order-based production strategies help reduce the waste of raw materials, while the use of social media is effective for promotion. However, reliance on one major supplier and online distribution platform poses risks that need to be managed.